2016
DOI: 10.1002/pen.24440
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness and foam morphology of cellulose acetate sheets foamed with 1,3,3,3‐tetrafluoropropene

Abstract: Cellulose acetate (CA) is a bio-based polymer suitable to replace foamed polystyrene (PS) in packaging applications. Foam trays can be produced by thermoforming of extruded sheets foamed with physical blowing agents. In this paper, the effects of various process settings and the calibration of the sheet on foam morphology and surface quality of extruded CA sheets are presented. Different contact cooling options were applied in order to investigate their influence on surface roughness, density, and morphology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Because CA is expandable in a similar way to polystyrene, there are available studies in which surface roughness and foam morphology of cellulose acetate sheets have been compared with PS [235], and a few papers are present on their blending [236,237].…”
Section: Hybrid Blends Based On Bio-based and Fossil Fuel-derived mentioning
confidence: 99%
“…Because CA is expandable in a similar way to polystyrene, there are available studies in which surface roughness and foam morphology of cellulose acetate sheets have been compared with PS [235], and a few papers are present on their blending [236,237].…”
Section: Hybrid Blends Based On Bio-based and Fossil Fuel-derived mentioning
confidence: 99%
“…An analysis of publications on the production of flat polymeric films [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] showed that majority of them are devoted to numerical and experimental modeling of separate stages of their production process. The focus on the process of preparation of polymer melt in the extruder [7][8][9][10], as well as the process of orientation of semi-finished film on the section from the extrusion head to the cooling drum [11][12][13][14][15][16].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In research [19], analysis of the effect of drum temperature on the structure of the resulting polymeric material was carried out, however, analysis of mutual influence of polymer and the drum on a change in their temperature was not considered.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…10 Nanomaterials not only improve the morphology and properties of solid polymers but also act as a nucleating agent in the foaming process of these polymers which leads to the decrease of cell size and increase of cell density. [11][12][13][14][15] The first development of microcellular foams was carried out in the early 1980s using the solid-state foam method. 16 After the introduction of microcellular foams by Martini et al 17 in 1981, in 1993, Park 18 researched microcellular foam production systems.…”
Section: Introductionmentioning
confidence: 99%